2006
DOI: 10.1103/physrevb.74.075335
|View full text |Cite
|
Sign up to set email alerts
|

Core-level photoemission study of thallium adsorbed on aSi(111)(7×7)surface: Valence state of thallium and the charge state of surface Si atoms

Abstract: , Core-level photoemission study of thallium adsorbed on a Si (111) The coverage-dependent valence state of Tl adsorbed on a Si͑111͒-͑7 ϫ 7͒ surface and the coverage dependence of the charge states of surface Si atoms have been investigated by high-resolution core-level photoelectron spectroscopy. Although two different reconstructions were observed in low-energy electron diffraction at different coverages, a ͑1 ϫ 1͒ pattern at a Tl coverage of 1 monolayer ͑ML͒ and a ͑ ͱ 3 ϫ ͱ 3͒ pattern at a coverage of 1 / 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The Tl 5d positions in Fig. b are indicative of Tl+1 in TlBr and Tl+3 in Tl2O3 , while the small feature at higher energy represents Tl0 metal and is consistent with the composition analysis of Tl‐rich regions. We note that the TlBr Tl 5d positions reported in Table differ from previous experimental reports by 0.4 eV (see Table ), but these studies were not supplemented by theoretical calculations and include the uncertainty in identifying the true VBM from the XPS valence band edge .…”
Section: Resultssupporting
confidence: 79%
“…The Tl 5d positions in Fig. b are indicative of Tl+1 in TlBr and Tl+3 in Tl2O3 , while the small feature at higher energy represents Tl0 metal and is consistent with the composition analysis of Tl‐rich regions. We note that the TlBr Tl 5d positions reported in Table differ from previous experimental reports by 0.4 eV (see Table ), but these studies were not supplemented by theoretical calculations and include the uncertainty in identifying the true VBM from the XPS valence band edge .…”
Section: Resultssupporting
confidence: 79%
“…This surface state originates from the hybridization between a single Tl 6p electron and one electron of the dangling bond of surface Si atom. (The 6s 2 electrons of the Tl atoms act as an inert pair and are inactive in the Tl-Si bonding due to the monovalent character of the Tl atoms [22,23].) This means that there is no orbital degeneracy in the observed surface-state band, and, therefore, the splittings observed at around k || = 0.5Å -1 and at around theK point are splitting between spin subbands.…”
Section: Resultsmentioning
confidence: 87%
“…Tl atoms are adsorbed on the T4 site of the (1 × 1) unreconstructed surface as shown in Fig. 1(a) [22,23], leading to a three-fold symmetric structure with mirror planes in the [1 12] this surface structure leads theK (andK ) point of the surface Brillouin zone (SBZ) to have a C 3 symmetry, a threefold symmetry without mirror plane since these points do not lie on the mirror plane ( Fig. 1(b)).…”
Section: Introductionmentioning
confidence: 99%
“…34 However, a recent core-level photoemission study on Tl adsorbed on Si(111)-7 × 7 showed that the Tl 5d core level was the same for the 1 × 1 and √ 3 × √ 3 phases, the authors concluding that there is no variable valence effect for Tl on an Si(111) surface. 35 …”
Section: Methodsmentioning
confidence: 97%